Pembelajaran IPS Dalam Manifestasi Keterampilan Abad 21 di MTs Nurul Huda Bantur Malang - Maslahah, Wafiyatu; Lailatul Rofiah,; Durorul Makrifah, (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2022)
Social studies learning in the 21st century must be carried out properly and can realize students' skills as provisions in society both now and in the future and are able to answer global challenges. The research contains the objectives to determine: (1) Social studies learning planning in the manifestation of 21st century skills in MTs. Nurul Huda Bantur Malang, (2) Implementation of social studies learning in the manifestation of 21st century skills in MTs. Nurul Huda Bantur, (3) Evaluation of social studies learning in the manifestation of 21st century skills in MTs. Nurul Huda Bantur. The approach used in this research is a qualitative approach with a descriptive type. The results showed that; 1) Social studies learning planning in the manifestation of 21st century skills such as prota, promissory note, lesson plans, and syllabus are appropriate. 2) Implementation of social studies learning in the manifestation of 21st century skills in MTs. Nurul Huda has been in the process of realizing active students by learning using the discussion method that tries to encourage communication skills, but the lecture method has not realized these skills. 3) Evaluation of learning in MTs. Nurul Huda Bantur Malang teacher evaluates students using several tests, namely diagnostic tests, formative tests, and summative test. Based on the results of this study, it was concluded that social studies learning at MTs Nurul Huda Bantur Malang has been in the process of realizing 21st century skills but still needs to be improved in terms of implementation active and interactive learning.